Management Theory and Research: Potential Contribution to Public Policy and Public Organizations - Hitt, Michael A. (Academy of Management Journal, 2005)
The article discusses way in which management theory and research can be applied to the public realm. A part of tackling unemployment involves encouraging the growth of new and innovative firms, and management theory has much to say about the importance of human capital that makes such firms possible. Research into international management provides insights into globalization and multinational companies. Theories of organizational behavior are very applicable to the administration of public bodies.